The effect of curricular activities on learner autonomy: the perspective of undergraduate mechanical engineering students. (2nd January 2016) - Duarte, M.; Leite, C.; Mouraz, A.
Abstract : This study researches how first-year engineering students perceived the influence of curricular activities on their own learning autonomy, measured with an adaptation of the Personal Responsibility Orientation to Self-direction in Learning Scale (PRO-SDLS). Participants were questioned to assess the influence of the teacher's role. The results indicate that learners' characteristics (motivation and self-efficacy) contribute more to learner autonomy (LA) than the teaching–learning transaction (control and initiative), as in the original PRO-SDLS validation. The most autonomous learners presented higher values in all LA components and dimensions, but the differences were greater in motivation and initiative. The participants with higher LA were not as dependent on the teacher, regarding assessment, the completion of classroom tasks and deadlines. Regardless of the degree of autonomy in learning, all participants viewed teachers as the main source of information. Therefore, LA plays an important role in teaching activities planning. Suggestions for adjustments and more flexible learning scenarios are formulated.